(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Examining the use of secondary-based approaches, such as phonetic guides, audiovisual aids, and pronunciation software, to teach English pronunciation in multicultural classrooms is the focus of this research. The use of these methods allows for student autonomy in practice, accommodates a wide range of linguistic backgrounds, and enhances phonetic correctness without the need for specific teacher training. The results demonstrate the efficacy of secondary-based approaches in improving pronunciation abilities, which promotes flexibility and inclusion in many educational settings. Our primary topics of discussion include the following: the significance of proper pronunciation, factors influencing its acquisition, inadequate self-assurance, inadequate education and training, limited time, and methods for instructing students in proper pronunciation.